Risk Analysis on The Construction Project of The 150 KV Bangkalan High Voltage Transmission Network - Mario Hartono; I Putu Artama Wiguna (Journal of Economics and Business UBS, 2023)
Electricity project implemented by PT. PLN (Persero) UIP JBTB is a construction project of the High Voltage Transmission Network and High Voltage Cable Channel 150 kV Bangkalan. The construction will certainly stretch across various terrains that have various levels of risk in the construction process. In addition, the construction project of the High Voltage Transmission Network and High Voltage Cable Channel 150 kV is a very complex project so that each stage has different obstacles so that it has the potential to have high risks in its implementation. The risk management will be based on SNI 8615:2018 ISO 31000:2018 regarding Risk Management – Guidelines and SNI IEC/ISO 31010:2016 Risk Management – Risk Assessment Techniques. The risk management process begins with determining the scope, context and risk criteria and then proceeds with the risk assessment process which includes identification, analysis, risk evaluation and risk treatment. This research was conducted to identify the risks that arise in the High Voltage Transmission Network and High Voltage Cable Channel 150 kV Bangkalan transmission development project and formulate the most effective response for each extreme, very high and high risk category of the project. The risk analysis of the Transmission Network project was carried out using a qualitative method to obtain a risk category. At risk that have extreme, very high, and high categories are risks that cannot be tolerated and a quantitative analysis will be carried out using the Expected Monetary Value method as measured data. Furthermore, with the Decision Tree Analysis diagram, several alternative risk treatment branches will be obtained which will then be analyzed using the multiplication of the response success value with the cost impact value in order to obtain the most effective treatment option. The results of the risk treatment will be categorized into risk mitigation, transferring risk, and accepting risk and the result of residual risk will be known through testing the effectiveness of handling risk treatment. The highest risk in this study is the risk of less than optimal contractor performance which causes project completion to be late with risk treatment by means of the good/services provider process being selected through an auction process which is included in the list of selected providers. The recording the risk register is also carried out as a database in risk analysis research on the construction project of the 150 kV Bangkalan high voltage transmission network.